2022
DOI: 10.3389/fendo.2022.803471
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Replacement Treatment for Frozen-Thawed Embryo Transfer With or Without GnRH Agonist Pretreatment: A Retrospective Cohort Study Stratified by Times of Embryo Implantation Failures

Abstract: ObjectiveTo evaluate the efficacy of the long-acting gonadotropin-releasing hormone agonist (GnRH-a) administration before hormone replacement treatment for frozen-thawed embryo transfer in women with different times of embryo implantation failures.MethodsA retrospective cohort study was performed between January 2015 and December 2019. A total of 9263 women who underwent frozen-thawed embryo transfer were included in the study. The study is divided into three parts based on the times of embryo implantation fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Endometrial thickness is one of the markers of endometrial receptivity. Before adjustment, The endometrium in the GnRHa-HRT group was thicker than that in the HRT group, which is in line with many previous researches (15,39,40). Some recent studies suggested that it is oestrogen supplementation without GnRH-a suppression that may lead to an increase in luteinizing hormone (LH), which ultimately has a detrimental effect on endometrial receptivity (23,41,42).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Endometrial thickness is one of the markers of endometrial receptivity. Before adjustment, The endometrium in the GnRHa-HRT group was thicker than that in the HRT group, which is in line with many previous researches (15,39,40). Some recent studies suggested that it is oestrogen supplementation without GnRH-a suppression that may lead to an increase in luteinizing hormone (LH), which ultimately has a detrimental effect on endometrial receptivity (23,41,42).…”
Section: Discussionsupporting
confidence: 77%
“…However, it is yet unclear whether HRT with GnRHa pre-treatment can improve reproductive outcomes. A recent clinical study suggests that pre-treatment of GnRH-a significantly improves the live birth rate in patients with multiple failed embryo implantation (15). Moreover, some studies indicate that the use of GnRH-a can improve endometrial receptivity (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…First, although the GnRH agonist pretreatment was traditionally used in endometriosis, this has not become a routine of practice in infertility centers in China. In contrast, GnRH agonist pretreatment before FET cycles was also widely used in various populations including women with recurrent implantation failure, [ 11 ] elderly patients, [ 12 ] and polycystic ovary syndrome [ 13 ] ; all the studies cited were conducted in the Chinese population. Second, reducing the time to pregnancy is an important factor to consider when making clinical decisions; maximizing the chances of transferring the embryo in the fresh cycle has been the goal for clinicians in all of the four centers in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For frozen-thawed embryo transfer (FET), hormone replacement therapy was used for endometrial preparation as previously described [24]. Oral estradiol valerate (4-6 mg/d; Progynova, Bayer, Germany) was commenced from the 3rd day of menstruation.…”
Section: Ivf Proceduresmentioning
confidence: 99%